2018
DOI: 10.15446/acag.v67n3.67377
|View full text |Cite
|
Sign up to set email alerts
|

Soil humidity and evapotranspiration under three coffee (Coffea arabica L.) planting densities at Naranjal experimental station (Chinchiná, Caldas, Colombia)

Abstract: El café es un cultivo dependiente del agua disponible en el suelo, bien sea a través de la lluvia o del riego, ya que ésta tiene un marcado efecto en la productividad y la distribución de la cosecha. Conocer el efecto de la distancia entre plantas sobre el comportamiento de la humedad en el suelo y el consumo de agua, influye en las prácticas agronómicas del sistema productivo del café, entre ellas: la densidad de siembra, la fertilización, y las épocas de siembra. El estudio se realizó en la Estación Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…In this research, the soil water potencial (Ψs) varied because of time and not of the PD (Figure 1), and the differences in time were related to changes in precipitation. The results contrast with those reported by Bermúdez-Florez et al (2018) and Honda et al (2019), those who found that low PDs were related to high soil moisture due to low water consumption. This behavior can be attributed to the fact that arracacha adjusts the root growth based on intraspecific competition in such a way that root tissue area in the soil does not change according to PD.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this research, the soil water potencial (Ψs) varied because of time and not of the PD (Figure 1), and the differences in time were related to changes in precipitation. The results contrast with those reported by Bermúdez-Florez et al (2018) and Honda et al (2019), those who found that low PDs were related to high soil moisture due to low water consumption. This behavior can be attributed to the fact that arracacha adjusts the root growth based on intraspecific competition in such a way that root tissue area in the soil does not change according to PD.…”
Section: Discussioncontrasting
confidence: 99%
“…The leaf temperature variability indirectly estimates transpiration and gs, indicating water deficit (Biju et al, 2018) that could be generated by the effect of high PD (Bermúdez-Florez et al, 2018;Honda et al, 2019). The leaf temperature depression (LTD) did not show significant differences between PDs except for 240 DAS in the PD of 30,000 plants ha -1 (Figure 5A), and this was related to the water use efficiency (WUEi) (Figure 5C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the soil moisture in shaded sites oscillated around 50%, which is the limit for water excess, from July to November (Figure 6). Water deficit was defined as <30% of volumetric soil moisture, and water excess at >50%, as in the study by [48].…”
Section: Coffee Stem Diameter Increment and Soil Moisturementioning
confidence: 99%
“…In this sense, Bermúdez‐Florez et al. (2018) analyzed differences in the behavior of volumetric soil moisture with respect to three different spatial arrangements, obtaining evidence of the influence of density sowing and seasonal atmospheric conditions on ET c . The eddy covariance (EC) method is a tool used worldwide to estimate ET c through energy balance, integrating the soil–plant atmosphere components.…”
Section: Introductionmentioning
confidence: 99%